Covid-19's Impact on the Liturgical Climate - Mathew, John (Asian Horizons, 2024)
One of the characteristics of Liturgy is that it is dynamic and ever- changing. This is due to the fact that both the human being and the universe are constantly changing. The Liturgy must adapt to changing conditions in order to stay relevant to today's society. Covid's doggedness has changed the manner of life human beings lived. The Roman Liturgy has the similar impact. It is not the first time in the church's history that change has occurred, and this article explains that change is a natural feature of the Catholic Liturgy that should not be regarded with suspicion but rather as an integral element of its character. In this presentation, the author has made an honest attempt to pinpoint a few of the recent changes that have happened as a consequence of Covid-19's effect.